A Smart IDE for Robotics Research - Sudip Chakraborty; P. S. Aithal (International Journal of Management, Technology and Social Sciences (IJMTS), 2022)
Purpose: We see the robot is engaged in every task, from the hazardous industrial environment to the floor cleaning. We are benefited directly or indirectly from robots in our everyday life. This is the untired efforts of many Robot researchers who play a significant role behind the scenes. They pass lots of tests before releasing the robot for humans. Most of the test procedure is to send the command from the IDE to the robot. The researcher generally feels two types of constraints. One is various IDE. They spend lots of time finding the tool’s location for different robot vendors with their IDE. Another one is, sometimes the proprietary robot IDE is not too fit for robot researchers. They need some customizable IDE. But in the close source application is not possible to customization. Here we described a procedure so that our two constraints can be solved. We developed a smart robotic IDE that can operate various robots, introducing a hardware abstraction layer. This IDE can also be configured in every aspect. It is an open-source application. The robot researcher can easily customize it according to their need. Design/Methodology/Approach: We create a GUI application in C# inside the visual studio community edition 2022. The main UI thread is integrated with file handling, programming interface, and various robot object. Here we created a couple of objects. In this way, we can make any new robot object. The object is exposed on the GUI element. Selecting any robot, we can send the available command through the terminal or programming interface. Findings/Result: Sometimes, robot researchers must break some impenetrable barrier for their research needs. But need lots of effort to develop some custom application to interact with robot or automated device. Through this research work, we provide helpful information so they can integrate their robot easily. Compared to other available open-source or closed-source applications, this application will take less time to debug and solve the issue at the earliest. Originality/Value: The smart IDE makes research work better and faster. We need complete freedom to interact with robots or automated devices. The industry standard robots have their IDE to interact with their robot. Sometimes times more flexibility makes work easy. In this scenario, our approach can provide us with better flexibility to work. By following this procedure, the researcher can get some unique benefits for their research work. Paper Type: Simulation-based Research.